2017
DOI: 10.1016/j.drugpo.2017.07.021
|View full text |Cite
|
Sign up to set email alerts
|

High HCV cure rates for people who use drugs treated with direct acting antiviral therapy at an urban primary care clinic

Abstract: Background Though direct acting antivirals (DAAs) promise high cure rates, many providers and payers remain concerned about successful treatment for people who use drugs (PWUD), even among those engaged in opioid agonist treatment (OAT). The efficacy of DAAs among PWUD in real-world settings is unclear. Methods We conducted a cohort study of patients initiating HCV treatment between January 2014 and August 2015 (n = 89) at a primary care clinic in the Bronx, NY. Onsite HCV treatment with DAAs was performed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
91
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(98 citation statements)
references
References 28 publications
6
91
0
1
Order By: Relevance
“…Extensive support for patients including peer support and social and psychological support was particularly important to ensure treatment adherence in interferon‐based treatment because of the long duration and toxicity of the treatment. As the DAA treatment is shorter treatment duration (8‐12 wk) and has fewer side effects, these support arrangements are more applicable for some patients, particularly PWID, patients who are suffering mental health problems, and socially complex and isolated patients …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extensive support for patients including peer support and social and psychological support was particularly important to ensure treatment adherence in interferon‐based treatment because of the long duration and toxicity of the treatment. As the DAA treatment is shorter treatment duration (8‐12 wk) and has fewer side effects, these support arrangements are more applicable for some patients, particularly PWID, patients who are suffering mental health problems, and socially complex and isolated patients …”
Section: Discussionmentioning
confidence: 99%
“…Linkage with the dispensing pharmacy, having peers as champions of treatment, multidisciplinary teams, and linkage with HCV tertiary services and specialists were also more particularly important in interferon‐based treatments. However, there is still perceived benefits in the era of DAAs …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study failed to describe the study participants and setting in detail, one study did not clearly mention how the exposure (receiving care at the community settings) was measured . The majority of studies failed to address confounders such as patients’ socioeconomic characteristics, HIV or HBV co‐infections, history of HCV treatment and types of healthcare providers . The other criteria (standard criteria for measuring the condition, valid and reliable way for measuring the outcomes and appropriate statistical analysis) were met by all studies.…”
Section: Resultsmentioning
confidence: 99%
“…Whilst adherence to DAA treatment in clinical trials has been extremely high, there are existing concerns that adherence rates will drop in real‐world settings, particularly among those with indicators of social marginalization, including PWID . However, thus far real‐world studies have demonstrated relatively high DAA treatment adherence among PWID, those with mental health comorbidities and those experiencing homelessness, particularly when treatment is administered through integrated care, community‐based or nurse led programs or in conjunction with adherence support . Sensitive patient‐reported outcome measures, which capture mental health, relationships with healthcare and social isolation may be used to link individuals with appropriate care in order to maximise adherence.…”
Section: Measuring the Impact Of Daasmentioning
confidence: 99%